The Disease Spectrum and Influencing Factors of NICU in Xiangxi, Underdeveloped Area of China: A 9-Year Retrospective Study - Xie, Fen; Zhu, Yuhua; Chen, Lulu; Han, Ruyi; Shu, Qingxia; Chen, Zheng-ying; Li, Jinxiu (Frontiers in Pediatrics, 2022)
Objective: Investigation of the basic conditions and disease spectrum in neonatal intensive care unit (NICU) from 2012 to 2020, in the underdeveloped area of Xiangxi, China. Methods: All newborns (N=16,094) admitted to the NICU of a hospital in the Xiangxi area from 2012 to 2020 were selected for the retrospective study. Results: The average male/female ratio was 1.43:1, with 9482 males and 6612 females admitted to the NICU. The sample comprised 41.02% premature infants, and 56.52% had been delivered via cesarean delivery (CD). The most prevalent diseases diagnosed in the NICU were jaundice (22.01%), respiratory (18.45%) and neurological diseases (17.54%). Over the 9-year study window, the prevalence of jaundice and cardiovascular diseases increased, while respiratory and neurological diseases became less frequent. The prevalence of other diseases remained unchanged. Prevalence of neonatal diseases is influenced by patient sources (whether from the same hospital or transferred from outside the hospital), delivery methods, gestational age, gender and birth weight (p< 0.05). The prevalence of neonatal diseases was significantly higher in males, infants born via CD and induced labor, and in infants of lower gestational age and birth weight. Conclusion: The study contributes in-depth information about infant characteristics in an NICU in an undeveloped region of China. 1) In the past 9 years, the average proportion of premature infants in the NICU decreased to 37.38% in 2020, but this figure remains higher than the Chinese national average of 26.2%. Similarly, the CD rate is higher than the Chinese average. 2) The spectrum of neonatal diseases in the NICU in Xiangxi area is drawn, included jaundice, respiratory and neurological diseases, primarily. 3) Through statistical analysis, it is found that the types and prevalence of neonatal diseases are closely related to different gender, gestational age, patient sources, delivery methods and birth weight . 4) Newborns of specific gestational age, birth weight and delivery method should be considered “at-risk” and targeted in the formulation of preventive measures. There is a great need to improve the diagnosis and treatment of neonatal diseases—and perinatal health care in general—to ensure improved outcomes for newborns admitted to NICUs in underdeveloped regions.